2016
DOI: 10.1007/s00468-016-1416-3
|View full text |Cite
|
Sign up to set email alerts
|

Cryopreservation changes the DNA methylation of embryonic axes of Quercus robur and Fagus sylvatica seeds during in vitro culture

Abstract: Key message Dehydration and cryo-stress (2196°C) caused a greater increase in the DNA methylation of embryonic axes (EAs) of beech seeds (tolerant to both stresses) than in EAs of oak (sensitive to both stresses). Simultaneously, in vitro survival of cryopreserved beech EAs was also significantly higher than in those of oak. Abstract DNA methylation plays a key role in the regulation of growth and differentiation in plants. The present study focused on global DNA methylation of embryonic axes (EAs) isolated fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 58 publications
0
7
0
Order By: Relevance
“…In desiccation-sensitive recalcitrant seeds, the use of dry seeds for storage is not possible because of the loss of seed viability following drying. Thus, the use of cryoprotectants is required to enabled cryopreservation of tissues isolated from recalcitrant seeds (Chmielarz et al 2011;Nuc et al 2016;Gaidamashvili et al, 2019). The present study revealed that seeds of M. boninensis have high desiccation tolerance, which is common among orthodox seeds, including Morus species (Kew Royal Botanic Gardens, 2008; https://data.…”
Section: Discussionmentioning
confidence: 83%
“…In desiccation-sensitive recalcitrant seeds, the use of dry seeds for storage is not possible because of the loss of seed viability following drying. Thus, the use of cryoprotectants is required to enabled cryopreservation of tissues isolated from recalcitrant seeds (Chmielarz et al 2011;Nuc et al 2016;Gaidamashvili et al, 2019). The present study revealed that seeds of M. boninensis have high desiccation tolerance, which is common among orthodox seeds, including Morus species (Kew Royal Botanic Gardens, 2008; https://data.…”
Section: Discussionmentioning
confidence: 83%
“…Hao et al (2001) associated cryopreservation-induced demethylation events to the increased root capacity of apple shoots observed after cryopreservation. Furthermore, Nuc et al (2016) studied DNA methylation after cryopreservation of embryonic axes isolated from seeds of pedunculate oak ( Quercus robur ) and European beech ( Fagus sylvatica ), and reported different methylation status depending on their tolerance (beech) or recalcitrance (oak) to dehydration. The loss of embryogenic potential observed in long-term subcultures of Quercus alba was associated by Corredoira et al (2017) to an increase in DNA methylation, and therefore might account for the lower maturation rates observed in aged maritime pine embryogenic lines.…”
Section: Discussionmentioning
confidence: 99%
“…For those species with the shortest longevity predictions, such as F. sylvatica and U. glabra, we recommend retest intervals at least every 5 years and recollection where necessary as well as further research into alternative storage methods such as cryo-storage. Successful cryo-storage has already been reported for seeds of a number of temperate tree species, including A. glutinosa (Chmielarz, 2010a), C. betulus (Chmielarz, 2010b), B. pendula (Chmielarz, 2010c), U. glabra (Chmielarz, 2010d), F. excelsior (Chmielarz, 2009), M. sylvestris (Michalak et al, 2015) and seeds and embryonic axes of F. sylvatica (Chmielarz, 2007;Nuc et al, 2016).…”
Section: Discussionmentioning
confidence: 99%